Modeling of Sediment Transport at Sungai Mersing By Using HEC-RAS - Mohd Nasir, Muhammad Luqman; Abustan, Muhammad Salleh (Recent Trends in Civil Engineering and Built Environment, 2021)
Sungai Mersing is located in the state of Johor, close to the town of Mersing, where large amounts of rain during the monsoon season wil be subjected to the sediment transport process. The river responds by increasing or decreasing sediment carrying capacity, changing the cross section of the channel, erosion and deposition along the channel, all of which have an impact to on river bank stability over time. This research is to model on the sediment transport at Sungai Mersing using Hydrologic Engineering Center River Analysis System (Hec Ras) for analysis more detail in analysis the river. There is a few data that required to gain all the analysis on sediment transport which are catchment area, precipitation data, geometric data and sediment data. The analysis that had been made can be done using various way of transport function in the Hec-Ras can be done using various way of transport function in the software. This also to control and predicting the river behavior.  This control is to take effective measurement in eliminate any associated threats and consequently in order to improve the river system. In general, analysis of river could be one of the complicated topic in the river engineering but for this case we using Hec-ras software enabled us to resolve the equation of sediment transport and hydraulic issue vie computer simulation and modelling.